2023
DOI: 10.1136/bcr-2022-251962
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse proliferative glomerulonephritis in a patient with COVID-19 infection

Abstract: COVID-19 primarily presents with respiratory involvement. Extrapulmonary manifestations as the sole manifestation also occur although rare. The kidney, being one of the organs with the greatest number of ACE receptors, is usually reported as part of multiorgan involvement. We report an early adolescent boy who presented with nephrotic–nephritic syndrome with severe kidney dysfunction from COVID-19 infection. He had low C3 and undetected antineutrophil cytoplasmic antibodies, antinuclear antibody and antistrept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Mechanism of injury noted from autopsy studies revealed evidence of viral infection in innate monocytes, macrophages, NK (natural killer) cells, evidence of viral replication in renal parenchymal cells, which was thought to cause tissue damage in the form of ATN, and glomerulosclerosis [ 111 ]. Other suggested mechanisms include hypoxia, hypoperfusion of kidneys causing ATN, immune complex deposition of viral particles in the kidneys [ 109 ], and induction of a proinflammatory state [ 98 ].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Mechanism of injury noted from autopsy studies revealed evidence of viral infection in innate monocytes, macrophages, NK (natural killer) cells, evidence of viral replication in renal parenchymal cells, which was thought to cause tissue damage in the form of ATN, and glomerulosclerosis [ 111 ]. Other suggested mechanisms include hypoxia, hypoperfusion of kidneys causing ATN, immune complex deposition of viral particles in the kidneys [ 109 ], and induction of a proinflammatory state [ 98 ].…”
Section: Reviewmentioning
confidence: 99%
“…Diverse renal manifestations reported worldwide include acute tubular necrosis (ATN), collapsing focal segmental glomerulosclerosis, albuminuria, hematuria, electrolyte derangements [98], minimal change disease, crescentic glomerulonephritis, thrombotic thrombocytopenic purpura (TTP), atypical hemolytic uremic syndrome (aHUS), IgA nephropathy, renal vein thrombosis, diffuse proliferative glomerulonephritis, acute kidney injury [106][107][108][109][110].…”
Section: Renal Manifestationsmentioning
confidence: 99%
“…Renal manifestations: Diverse renal manifestations reported worldwide include acute tubular necrosis (ATN), collapsing focal segmental glomerulosclerosis, albuminuria, hematuria, electrolyte derangements (98), minimal change disease, crescentic glomerulonephritis, thrombotic thrombocytopenic purpura (TTP), atypical hemolytic uremic syndrome (aHUS), IgA nephropathy, renal vein thrombosis, diffuse proliferative glomerulonephritis, acute kidney injury (106)(107)(108)(109)(110).…”
Section: Skinmentioning
confidence: 99%
“…Mechanism of injury noted from autopsy studies revealed evidence of viral infection in innate monocytes, macrophages, NK (natural killer) cells, evidence of viral replication in renal parenchymal cells which was thought to cause tissue damage in the form of ATN (acute tubular necrosis), and glomerulosclerosis (111). Other suggested mechanisms include hypoxia, hypoperfusion of kidneys causing ATN, immune complex deposition of viral particles in the kidneys (109), and induction of a proinflammatory state (98).…”
Section: Skinmentioning
confidence: 99%
“…The most common pathogenesis involved in COVID-19-induced AKI is the activation of the complement cascade, acute and chronic inflammation with immune cell infiltration in the kidney, hypercoagulopathy, formation of microvascular thrombi, endothelial dysfunction (due to vascular endotheliitis), pigment nephropathy, and mitochondrial dysfunction. AKI is also caused by the direct invasion of the SARS-CoV-2 virus into podocytes and proximal convoluted tubule involving angiotensin-converting enzyme 2 (ACE2) and transmembrane protease, serine 2 (TMPRSS2) [1,[11][12][13][14][15][16] (Figure 1).…”
Section: Acute Kidney Injury In Covid-19mentioning
confidence: 99%